The Politics of Gender in Colonial Korea: Education, Labor, and Health, 1910-1945 - Choi, Chungmoo (Asian journal of women's studies, 2008)
University of California Press, 2008, 316 pages Chungmoo CHOI Upon entering the new millennium, starting with Choi Hye SU's What Did New Women Dream (Sinyeoseong-un Muoseu-l Kkumkkueotnunga) (2000), Korean feminist historians and culture critics have produced an appreciable number of studies on the life and history of women during the Japanese colonial period (1910-1945). The five chapters in this book comfortably straddle both the 1990s Marxist feminist scholarship-including the mobilization of unskilled or semi-skilled women's labor in the textile and chemical industry (Suh, 1989), the structural change of women's labor market (Kang, 1993) and the socialist women writers'narratives on women activism in the labor movement such as Kang Kyong-ae's The Human Problem (Ingan munje) (1933) set in Inchon in the 1930s-and the emerging feminist historiography of the 2000s, as mentioned above.